Screening patients at high risk for pancreatic cancer—Is it time for a paradigm shift?. Issue 5 (16th July 2019) - Lo, Winifred; Morris, Mackenzie C.; Ahmad, Syed A.; Patel, Sameer H.
Abstract: Pancreatic cancer remains leading cause of cancer‐related death in the United States. Patients with familial pancreas cancer, hereditary pancreatitis, known genetic mutations, and syndromes are deemed high risk for the development of pancreas cancer. Guidelines exist to help facilitate early diagnosis and treatment and these will be reviewed. Pancreatic cancer remains a leading cause of cancer‐related death in the United States. Patients with familial pancreatic cancer, hereditary pancreatitis, known genetic mutations, and syndromes are deemed high risk for the development of pancreas cancer. Guidelines have been made to help facilitate early diagnosis and treatment for these patients and these will be reviewed. The exact timing of initial screening depends not only on the individual risk factors but consists of endoscopic ultrasound and magnetic resonance cholangiopancreatography. The frequency of screening depends largely on the findings of initial imaging and the patient's clinical status. We suggest that providers make themselves knowledgeable of current screening recommendations and appropriately apply them. Further critical evaluation of ongoing research is necessary to amend these recommendations as more data and genetic testing becomes available.